(untitled) (INTEGRATION PROCEEDING, 2023)
This literature review examines the impact of Breast Care during pregnancy on the success of the lactation period inIndonesia. Despite achieving the strategic plan target of 50% for exclusive breastfeeding coverage, challenges remain in attaining higher rates. Factors such as lack of breastfeeding confidence, insufficient milk production, and breastfeeding complications contribute to the lower exclusive breastfeeding rate. To address these challenges, pregnant women are encouraged to practice Breast Care as preparation for the lactation period. The review includes 11 relevant journals, focusing on pregnant women’s knowledge and motivation regarding Breast Care. The findings indicate that increased knowledge and motivation among mothers positively influence the success of Breast Care. When pregnant women possess a good understanding of the importance of Breast Care and are motivated to implement it, they are more likely to experience favourable outcomes during the lactation period. The reviewed literature emphasizes the benefits of practicing Breast Care during pregnancy. Engaging in Breast Care activities such as nipple stimulation, maintaining proper hygiene, and regular breast examination contribute to smooth postpartum breast milk production. Pregnant women who consistently practice Breast Care often report timely and sufficient breast milk supply within the first 24 hours after giving birth. This early initiation of breastfeeding is crucial for establishing successful breastfeeding and promoting the overall health and well-being of both the mother and the infant. In conclusion, Breast Care during pregnancy significantly influences the success of the lactation period. Educating and motivating pregnant women about the importance and techniques of Breast Care is crucial for enhancing their knowledge and confidence in breastfeeding. Healthcare providers, lactation consultants, and support groups play a key role in providing the necessary education and support to pregnant women. By promoting the adoption of Breast Care practices during pregnancy, Indonesia can improve exclusive breastfeeding rates, leading to improved maternal and child health outcomes and overall well-being.